BUDIDAYA ULAT SUTERA DAN PRODUKSI BENANG SUTERA MELALUI SISTEM KEMITRAAN PADA PENGUSAHAAN SUTERA ALAM (PSA) REGALOH KABUPATEN PATI - Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2011)
This study aimed to determine the process of cultivation and silkworm silk yarn production in the Exploitation of Natural Silk (PSA) Pati Regaloh. The basic method of research used is descriptive method. Determining the location of the research conducted (purposive), the Concession Alam Sutera (PSA) Regaloh. The results obtained are Regaloh PSA has implemented a system of partnerships between employers and the surrounding farming community through the core system and plasma. Technically maintenance silkworms can be divided into two, namely the maintenance of mulberry plantation and silkworm breeding. The species planted mulberry is Morus multicaulis Regaloh PSA, Morus cathayana, Morus nigra, Morus alba and mulberry mixed types. Mulberry plant maintenance includes fertilizing, pendangiran (weeding), and trimming. Maintenance consists of maintenance silkworm caterpillars are small and large caterpillars. Harvesting is done after the silkworm cocoon mengokon for 6-7 days in the maintenance brak brak-large caterpillar. The processing of cocoons into silk yarn is divided into several stages, namely boiling, reeling, rereeling, pressing and packing. Keywords: cultivation of silkworms, silk yarn, partnership, PSA Regaloh